Variation of carbon isotope fractionation in hydrogenotrophic methanogenic microbial cultures and environmental samples at different energy status - Penning, Holger (Global change biology, 2005)
Methane is a major product of anaerobic degradation of organic matter and an important greenhouse gas. Its stable carbon isotope composition can be used to reveal active methanogenic pathways, if associated isotope fractionation factors are known. To clarify the causes that lead to the wide variation of fractionation factors of methanogenesis from H2 plus CO2 (), pure cultures and various cocultures were grown under different thermodynamic conditions. In syntrophic and obligate syntrophic cocultures thriving on different carbohydrate substrates, fermentative bacteria were coupled to three different species of hydrogenotrophic methanogens of the families Methanobacteriaceae and Methanomicrobiaceae. We found that C-isotope fractionation was correlated to the Gibbs free energy change (ΔG) of CH4 formation from H2 plus CO2 and that the relation can be described by a semi-Gauss curve. The derived relationship was used to quantify the average ΔG that is available to hydrogenotrophic methanogenic archaea in their habitat, thus avoiding the problems encountered with measurement of low H2 concentrations on a microscale. Boreal peat, rice field soil, and rumen fluid, which represent major sources of atmospheric CH4 , exhibited increasingly smaller , indicating that thermodynamic conditions for hydrogenotrophic methanogens became increasingly more favourable. Vice versa, we hypothesize that environments with similar energetic conditions will also exhibit similar isotope fractionation. Our results, thus, provide a mechanistic constraint for modelling the 13 C flux from microbial sources of atmospheric CH4